STRATEGI PEMASARAN CITILINK DALAM MEMENANGKAN PERSAINGAN DI PASAR INDONESIA - Imam Ozali; Charles AN; Yana Tatiana (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2025)
The Indonesian domestic aviation industry continues to experience significant growth in line with increasing public mobility and expanding regional access. Citilink, a subsidiary of Garuda Indonesia operating as a low-cost carrier (LCC), strives to strengthen its national market share through the implementation of adaptive and innovative marketing strategies. This study aims to analyze Citilink's marketing strategy to win the Indonesian domestic aviation market competition in 2024. Using a qualitative approach and descriptive methods, data were collected through interviews with Citilink management, observations in various operational areas, and secondary document reviews. The results show that Citilink consistently applies the marketing mix (7Ps) covering product, price, place, promotion, people, process, and physical evidence. Competitive pricing strategies, aggressive digital promotional campaigns, and collaboration with various industrial sectors and local governments are key to expanding market reach. Citilink positions itself as a "Smart Value Airline" that prioritizes a combination of affordable prices and quality service. Challenges faced include limited infrastructure, intense price competition, and public perception of LCC airline services. This study concludes that Citilink's marketing strategy is generally relevant to the characteristics of the Indonesian market and capable of enhancing its national competitiveness. These findings are expected to serve as a strategic reference for industry players and contribute to academics' development of aviation marketing studies.